Design and Optimization of Washing Machine for Value Innovation and Field Failure Rate (FFR) Reduction - Kaur, Jashanpreet (My University, 2022)
LG Electronics offers a fantastic opportunity for aspiring engineers to obtain useful exposure in such a big sector and that too in a really supportive and caring culture and people. Here is a summary of the course, despite the fact that the tremendous quantity of work completed and experience gained over the last year cannot be enumerated in a few lines. My project is titled as “DESIGN AND OPTIMIZATION OF WASHING MACHINE FOR VALUE INNOVATION AND FIELD FAILURE RATE (FFR) REDUCTION”. At the QA (WM) LGEIL, my work largely involved developing the concept and determining its viability for several other factors, as well as testing the various product components. Modelling is done for the new development and certain machine changes.. It also contains study of various electrical, electronic and mechanical components being used in goods and exploring new possibilities for improvement in quality or reduction in cos
Keywords: Field Failure Rate, Optimization, Smart Washing machine